An interventional study on the knowledge, attitude and practice on hand, foot and mouth disease among the parents or caregivers of children aged 10 and below at Nanga Sekuau resettlement scheme from 26th March to 10th June 2012 - Abu Zarin, bin Zahar; Yoganantham, a/l Kodiesarn; Teh, Thian Ping; Tee, Jie Xi; Sumayyah, binti Hashim; Sim, Joo Ching; Rebecca, anak Tulo; Rachel, Kamea; Nurul Shahirah, binti Abdul Shuko; Nurul Fadlin, binti Rosl; Nuraishah, binti Md. No; Nur Inani, binti Ahmad Tarmizi; et al. (Universiti Malaysia Sarawak (UNIMAS), 2012)
Hand, Foot and Mouth Disease (HFMD) is now considered an emerging infectious disease that affects the population worldwide. In order to cope with the high prevalence of HFMD in Malaysia, level of knowledge and awareness among the population should be assessed so that appropriate interventions can be carried out. The objective of this study was to study the knowledge, attitude and practice on HFMD among the parents or caregivers of children aged 10 years and below at Nanga Sekuau Resettlement Scheme from 26th of March to 10th of June 2012. The results obtained were then using as the baseline data to conduct an intervention beneficial to the community to enhance their level of knowledge, attitude and practice towards HFMD. Data collection was done by face to face interview using interview-based questionnaire. Data analysis was done using SPSS software version 20.0. Results showed that 61.1 % of the respondents had good knowledge, 52.2% had good attitude while 55.8% had good preventive practice towards HFMD. Analysis found a significant association between total knowledge score and the level of education (p<0.05). Similar significant association was found between total attitude score and leveJ of education (p<0.05) and marital status (p<0.05). However, no significant association was found between total practice score and socio-demographic characteristics. A positive correlation was found between the knowledge and attitude (p<O.OI) as well as attitude and practice (p<O.OOl). Post-intervention study showed significant improvement in the knowledge on mode of spread of HFMD (p<005), but no significant increase in the t~tal level of knowledge, attitude and practice (p>0.05). In conclusion, there is a great need for intensive intervention in order to enhance their awareness on HFMD among the respondents.